Diffuse reflectance spectroscopy for ultraviolet A protection factor measurement: correlation studies between in vitro and in vivo measurements - Ruvolo Jr, Eduardo; Chu, Melissa; Grossman, Florence; Cole, Curtis; Kollias, Nik (Photodermatology, photoimmunology & photomedicine, 2009)
Background/purpose: Assessing the ultraviolet (UVA) protection factor of sunscreen formulations has been discussed for the past 20 years. The purpose of this study is to correlate the measurements of the UVA protection factor value (PFA value) via in vivo diffuse reflectance spectroscopy (DRS) and to compare this method with the in vitro method of measuring the PFA value, as well as with the in vivo persistent pigment darkening (PPD) and PFA methodologies. Methods: The UVA protection factor via DRS technique was assessed in two clinical studies. The first study was performed in 12 subjects and the second one consisting of 10 subjects. All subjects in these studies had Fitzpatrick skin phototypes II–IV. DRS measurements were performed using a SkinScan spectrofluorimeter (Spex SkinScan, Yvon Horiba). The in vitro PFA measurements were performed using Labsphere™ UV‐1000s UV Transmission Analyzer. Results: The results obtained from the non‐invasive DRS studies were used to correlate with the in vitro testing and with the in vivo PFA/PPD multicenter study. A positive relationship (regression coefficient r2=0.90) of PFA values was found between in vitro PFA testing and the in vivo DRS testing. There was also a very good correlation (regression coefficient r2=0.99) between the in vivo PFA/PPD values and UVA protection factor obtained from the DRS method. Conclusion: This paper presents studies using the DRS technique to assess the UVA protection factor in different sunscreen formulae correlating with in vitro and in vivo PFA/PPD values. It is a fast method, non‐invasive and does not involve any subject irradiation. The technique is a good estimator for the in vivo UVA protection factor as well as a way to assess, in vivo, the photostability of sunscreen formulation in the UVA.